2020
DOI: 10.1364/ao.393643
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microplastics in a large water volume by integrated holography and Raman spectroscopy

Abstract: A noncontact method to identify sparsely distributed plastic pellets is proposed by integrating holography and Raman spectroscopy in this study. Polystyrene and poly(methyl methacrylate) resin pellets with a size of 3 mm located in a 20 cm water channel were illuminated using a collimated continuous wave laser beam with a diameter of 4 mm and wavelength of 785 nm. The same laser beam was used to take a holographic image and Raman spectrum of a pellet to identify the shape, size, and composition of material. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…This is one of the first demonstrations of flow-through counting and sizing of microplastics with differentiation of plastic and biological materials. Flow-through microplastic detection has been demonstrated via Raman spectroscopy and resistive pulse detection; however, Raman spectroscopy-based techniques did not measure the full fluid flow, allowing particles to flow through unanalyzed and therefore inaccurately counting microplastics. With impedance spectroscopy, measurements were high-throughput, with each particle in the flow cell for milliseconds. Since the impedance measurements are real-time, this approach could be used to divert microplastics for further analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the first demonstrations of flow-through counting and sizing of microplastics with differentiation of plastic and biological materials. Flow-through microplastic detection has been demonstrated via Raman spectroscopy and resistive pulse detection; however, Raman spectroscopy-based techniques did not measure the full fluid flow, allowing particles to flow through unanalyzed and therefore inaccurately counting microplastics. With impedance spectroscopy, measurements were high-throughput, with each particle in the flow cell for milliseconds. Since the impedance measurements are real-time, this approach could be used to divert microplastics for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Often, visual identification is used to separate microplastics from natural materials, , but significant misidentification errors can occur. ,,− Nile Red can aid in the detection of microplastics, , but biological particles can cause false detections. , The microplastic type can be identified with Raman spectroscopy, including Raman microspectroscopy ,, and Raman imaging, or with Fourier transform infrared (FTIR) spectroscopy, including attenuated total reflection-FTIR (ATR-FTIR) ,,, and FTIR imaging, ,,, or with pyrolysis gas-chromatography mass-spectrometry. ,, These polymer identification techniques are time-consuming and require expensive equipment. , To reduce the analysis time, a visual identification step or subsampling is often used, which can cause nonrepresentative results. ,,,,, Portable pyrolysis-mass spectrometry is rapid (5 min), but the biological material can interfere with the analysis, and particles are not individually quantified . Flow-through microplastic detection via Raman spectroscopy achieves higher throughput but cannot count microplastics accurately because the flow through the sensor is only partially analyzed. Biological particles can also interfere with Raman measurements . Pollard et al recently demonstrated the use of a flow-through resistive pulse sensor to detect microplastics shed from tea bags and differentiate them from rod and spherical algae …”
mentioning
confidence: 99%
“…36,51−54 Further analysis of the items classified as microplastic could be then carried out by spetroscopy methods to add specificity about the plastic material. 51,53,54 We believe the approach we proposed is robust against the large heterogeneity of scenarios that can be found in marine samples from different areas. For instance, microplastics' aging in seawater is not expected to worsen the performance.…”
Section: ■ Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Using Raman spectroscopy, identification of types of plastic pellets in a large water volume has been successfully performed. 24 Detection of flowing microplastics with the size of more than 100 µm has also shown to be possible. 25 These studies demonstrate the feasibility of Raman spectroscopy for screening of microplastics without extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to FT-IR spectroscopy, Raman spectroscopy has a big advantage in the analysis of submerged targets in water since visible and near-infrared (NIR) excitation laser beams penetrate further in water than ultraviolet (UV) and IR excitation light sources. Using Raman spectroscopy, the identification of types of plastic pellets in a large water volume has been successfully performed . The detection of flowing microplastics larger than 100 μm has also shown to be possible .…”
Section: Introductionmentioning
confidence: 99%